2023
DOI: 10.3390/w15162904
|View full text |Cite
|
Sign up to set email alerts
|

Flow Field and Gas Field Distribution of Non-Submerged Cavitation Water Jet Based on Dual-Nozzle with Concentric Configuration

Abstract: Cavitation water jet peening is an efficient and green surface treatment technology. The dual-nozzle can realize a cavitation water jet in air (non-submerged condition), which can be used for the surface treatment of large structures. The flow field characteristics of the dual-nozzle determine the cavitation effect. In this paper, the simulation of a cavitation water jet in air is carried out using Fluent software. The flow field characteristics containing velocity distribution, impact pressure, and gas phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The above equation includes the constant, linear, squared, and interaction terms, along with an error term. In Equation (7), n is the number of independent variables; ε is the total error; β 0 , β i , β ii , and β ij are the regression coefficients; and x is the investigation factor.…”
Section: Response Surface Methods Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The above equation includes the constant, linear, squared, and interaction terms, along with an error term. In Equation (7), n is the number of independent variables; ε is the total error; β 0 , β i , β ii , and β ij are the regression coefficients; and x is the investigation factor.…”
Section: Response Surface Methods Designmentioning
confidence: 99%
“…Relevant studies have shown that under the same conditions of pump pressure and flow rate conditions, the impact pressure of a cavitation jet is 8.6 to 124 times higher than that of a continuous jet [2][3][4]. Cavitation jet technology has wide applications in fields such as oil extraction, cleaning and rust removal, and metal surface strengthening [5][6][7].…”
Section: Introductionmentioning
confidence: 99%